Component-based TV regularization for X-ray tensor tomography - Seyyedi, Saeed; Wieczorek, Matthias; Sharma, Yash; Schaff, Florian; Jud, Christoph; Pfeiffer, Franz; Lasser, Tobias (Proceedings - International Symposium on Biomedical Imaging, 2016)
X-ray Tensor Tomography (XTT) is a recently developed imaging modality that provides reconstruction of X-ray scattering tensors from dark-field projections obtained in a grating interferometry setup. In this work we present a novel component-based total variation (TV) regularized reconstruction technique for XTT data. First results show promising qualitative improvements of the reconstructed tensors as well as reduced noise and reduced streak artifacts.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Computed Tomography; Sparse Regularization; Total Variation; X-ray Tensor Tomography